Corticosteroid versus Ozone Injections in Chronic Plantar Fasciitis: A Comparative Clinical Study - Rıdvan Işık; Emre Uzun; Muhammed Zahid Şahin (Sakarya Medical Journal, 2026)
Objective: Plantar fasciitis is a common degenerative condition causing chronic heel pain and functional limitation. Corticosteroid injections are widely used but carry potential adverse effects, whereas ozone therapy has emerged as an alternative with anti-inflammatory and regenerative properties.The aim of this study is to compare the efficacy of ultrasound-guided corticosteroid and ozone injections on pain, function, and quality of life in chronic plantar fasciitis.Methods: This retrospective cohort study included 59 patients unresponsive to conservative treatment. Patients received either a single corticosteroid injection (Group S, n=30) or three weekly ozone injections (Group O, n=29). Outcomes were assessed using the Numerical Rating Scale (NRS), Foot Function Index (FFI), and Short Form-12 (SF-12) at baseline, 1 month, and 3 months. Treatment response was defined as ≥50% reduction in NRS.Results: Both groups showed significant improvement over time (p<0.001). Pain reduction was similar at 1 month. At 3 months, corticosteroids resulted in lower NRS scores (p=0.024) and higher responder rates (70.0% vs. 31.0%, p=0.003). Corticosteroids provided greater short-term functional improvement, whereas ozone showed superior FFI scores at 3 months (p<0.001). SF-12 physical scores improved similarly; mental scores favored corticosteroids (p=0.025). No serious adverse events occurred.Conclusions: Both injections effectively improve pain, function, and quality of life in plantar fasciitis. Corticosteroids provide superior pain relief, while ozone may offer better long-term functional improvement. Treatment selection should be individualized based on clinical priorities.